Surgical repair of D-TGA with an aortopulmonary window and ventricular septal defects - Reddy,Srikrishna M (2010)
D-Transposition of great arteries with an aortopulmonary window is a rare congenital anomaly. We describe a case of D-Transposition of great arteries with an aortopulmonary window and multiple ventricular septal defects in a 5-month boy who underwent successful surgical repair.